Upaya Memperkuat Peran Koperasi dan UMKM sebagai Sokoguru dalam Mewujudkan Sistem Keadilan dan Keberlanjutan dalam Implementasi Ekonomi Kerakyatan - Septiana, Yuvi Putri (Maliki Interdisciplinary Journal, 2024)
In the last few decades, the contribution of cooperatives and Micro, Small and Medium Enterprises (MSMEs) to the Indonesian economy has continued to increase. This growth makes cooperatives and MSMEs the main supporters of the national economy in poverty alleviation and job creation, and are expected to become the mainstay in realizing a system of justice and sustainability in the implementation of the people's economy. Therefore, the development of cooperatives and MSMEs is a crucial part of the national development agenda which aims to strengthen the system of justice and sustainability in the implementation of the people's economy. So that several efforts are needed to strengthen and develop the role of cooperatives and MSMEs as the main pillars of realizing a system of justice and sustainability in the implementation of the people's economy such as through; increasing access to capital, increasing the capacity of Human Resources (HR), strengthening institutions and governance, strengthening the value chain and market access, government policy support, developing a sustainable ecosystem which is expected to strengthen and develop the role of cooperatives and MSMEs as mainstays in realizing a sustainable and equitable people's economic system.